An Analysis of the Adaptation of Greek Mythology in Disney+’s Percy Jackson and the Olympians (2023) (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research analyzes the adaptation of Greek mythology in Percy Jackson and the Olympians (2023) to understand how ancient myths are reimagined for a modern audience. The research objectives are to examine how classical myths are adapted for contemporary viewers and to explore the reinterpretation of mythological characters and themes in the Disney+ series. The population includes adaptations of Greek mythology in modern media, while the sample focuses on the Percy Jackson and the Olympians TV series (2023) and its original book series by Rick Riordan. The study employs qualitative methods, including textual analysis, character and thematic analysis, audience reception analysis, and comparative analysis with other adaptations such as The Lightning Thief (2010) and Blood of Zeus (2020), using data from primary, secondary, and tertiary sources. The findings reveal that the series humanizes mythological figures to address modern themes like identity, empowerment, and diversity, while balancing respect for the original myths with creative reinterpretations. It also highlights the educational potential of the adaptation and the challenges of maintaining mythological authenticity while engaging contemporary audiences.